Screening for extracellular synthesis of silver nanoparticles by bacteria isolated from Al-Halfaya oil field reservoirs in Missan province, Iraq - HASAN GHALI ABDULHASAN ALSHAMI; WIJDAN H. AL-TAMIMI; RASHID RAHIM HATEET (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Alshami HGA, Al-Tamimi WH, Hateet RR. 2022. Screening for extracellular synthesis of silver nanoparticles by bacteria isolated from Al-Halfaya oil field reservoirs in Missan province, Iraq. Biodiversitas 23: 3462-3470. Microorganisms that live in deep environments are thought to be adapted to the conditions of these environments and possess enzymatic systems that can be useful in scientific and commercial applications. The study aimed to isolate, identify, and screening of silver nanoparticles (AgNPs)-producing bacteria from five samples of produced water of the Al-Halfaya oil field reservoirs in Missan governorate, Iraq. The results revealed a total of 22 bacterial isolates were isolated and identified by morphological features and amplification of the 16S rDNA gene. The isolates are belonging to nine species, including Bacillus cereus strain DBA1.1, Bacillus thuringiensis strain MSP51, Neobacillus drentensis strain ROA042, Enterococcus faecalis strain 2674, Exiguobacterium mexicanum strain AB201, Klebsiella quasipneumoniae strain KP18-31, Klebsiella quasipneumoniae subsp. similipneumoniae strain 2437, Klebsiella pneumoniae strain IOB-L, and Acinetobacter lwoffii strain K34. The Gram-positive bacteria were the most dominant (55.56%), and the most frequent isolate was Klebsiella quasipneumoniae strain KP18-31 (63.64%). Six species out of nine species were recognized as AgNPs producing bacteria and B. cereus strain DBA1 was the best and most potent isolate in the synthesis of AgNPs. The phylogenetic tree was constructed depending on 16S rDNA gene sequences to determine the evolutionary relationship among the isolated bacteria.